Systematic Literature Review: Pengaruh Media Pembelajaran Digital pada Pembelajaran Tematik Terhadap Hasil Belajar Siswa SD - Hasna Nur Alifah; Umi Virgianti; Muhammad Imam Zamah Sarin; Dicky Amirul Hasan; Fina Fakhriyah; Erik Aditia Ismaya (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Education utilizes digital technology in supporting teaching and learning activities through learning media. This study aims to identify the influence of the use of digital learning media on thematic learning used for elementary school students. The research method used is SLR (Systematic Literature Review). The articles used in this study are seven national journal articles and have passed the criteria determined by researchers in the 2018-2023 period. Conton digital learning media that can be used by elementary school students in thematic learning include the Canva application, WhatsApp group, and Google Classroom which is supported by animations, learning videos, powerpoints, to digital comics. Based on the literature review conducted, it was found that the use of learning media that updates digital technology can improve student learning outcomes. This is evidenced by the ease of students in obtaining and understanding subject matter, minimizing boredom in students and increasing students' focus to digest the learning which of course can be adjusted to the needs and changes of today.